Recapsoma®: A Novel Mixture Based on Bergamot, Ipomoea Batatas, Policosanol Extracts and Liposomal Berberine for the Treatment of Hypercholesterolemia - Chiara Amante; Tiziana Esposito; Gianni Luccheo; Luigi Luccheo; Paola Russo; Pasquale Del Gaudio (Life, 2022)
Cardiovascular disease (CVD) is considered one of the major causes of mortality worldwide. Epidemiological studies have shown that regular consumption of phenols is inversely associated with cardiovascular disease, and the use of nutraceuticals and functional foods can provide protective, preventive, and possibly curative effects in CVD. A novel mixture of different natural substances named Recapsoma® (bergamot, liposomal berberine, Ipomoea batatas, oleuropein, polycosanols, and vitamin E) has been produced, and its anti-dyslipidaemic efficacy has been tested, specifically studying the in vitro effects on the mechanisms of action underlying cholesterol synthesis, triglycerides, and LDL-cholesterol oxidation. The work has demonstrated the ability of this herbal extract mixture to inhibit the action of PCSK, ACAT, PAP, and HMGR and to increase the LDL receptor (LDLR), underlying the synergistic effect of the mixture over the single components. Such results suggest that the Recapsoma® mixture could be used as a tool for controlling hypercholesterolemia, and an alternative to statins, especially for those patients with metabolic syndrome.